Quando as Avaliações Viram Bombas: Explorando a Dinâmica do Review Bombing nos Jogos no Metacritic - Ribeiro, Marcus Vinicius Guerra; Pimentel, Clara Andrade; Melo, Philipe de Freitas (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2024: Proceedings of the 30th Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2024.241744, 2024)
This study investigates the phenomenon of “Review bombing” on Metacritic, a platform for aggregating media reviews. Review bombs involve the deliberate posting of a large volume of negative reviews to alter the reputation of a media work, often driven by political, social, or creator-related disagreements. We collected extensive data from Metacritic, comprising 145K games and 1M reviews to understand and identify the characteristics of review bombing online. Using clustering techniques and analyzing various user and game-related metrics, we found that targeted games experience a significant increase in review volume, often with similar content and slightly higher toxicity, reflecting coordinated dissatisfaction campaigns. Additionally, the clustering achieved an F1-score of 0.5263, revealing particular challenges to categorizing this kind of attacks, such as the removal of evidence by platform moderation and difficulty in labeling minor attacks. The study highlights the need for robust mechanisms to detect and mitigate review bombs to preserve the integrity of review platforms and consumer trust.